Characterization of the complete mitochondrial genome of the Pohlia nutans M211 from Antarctica - Junhan Cao; Xihong Yang; Yanfeng Wang; Yingying He; Changfeng Qu; Jinlai Miao (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Pohlia nutans M211, sequenced using Illumina NovaSeq PE150, was 99864 bp in length. It encoded 65 genes, comprising 38 protein-coding genes, 24 tRNA genes and 3 ribosomal RNA genes. For these 38 PCGs, the most common start codon was ATG and the most common termination codon was TAA. The total GC content was 36.91% while the composition of A + T was 60.39%. Phylogenomic analysis indicated that P. nutans M211 was closely related to Mielichhoferia elongate.